Analisis Pusat Pertumbuhan dan Autokorelasi Spasial di Kalimantan: Studi Empiris di 55 Kabupaten/Kota, 2000–2012 - Pratiwi, Maria Christina Yuli; Kuncoro, Mudrajad (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
The paper identifies which districts in Kalimantan that become the growth poles and whether there has been spatial autocorrelation in 55 districts during 2000–2012. This study also explores which economic sectors will be leading sectors. The social-economic data were collected for 55 districts using quantitative methods, in particular: typology of Regent/City, spatial autocorrelation, overlay analysis, and structural transformation. The study finds: (1) there are 4 cities as the growth pole; (2) the economics growth concentration concentrated geographically in the eastern and western; (3) the mining sector is a leading and competitive sector; and (4) structural transformation does not occur in all districts.